2023
DOI: 10.1002/ajmg.a.63327
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of two recurrent missense mutations in the RS1 gene in two families with X‐linked retinoschisis from North India

Abstract: X‐linked retinoschisis (XLR) is a rare medical condition that involves in the splitting of neurosensory layers and the impairment of vision in the retina. In majority of the XLR cases, pathogenic variants in Retinoschisin 1 (RS1) gene have been implicated in males with an early age of onset during early childhood. In the present study, we have recruited two North Indian families having multiple affected male members, who were diagnosed with XLR. The entire protein‐coding region of RS1 was screened by PCR‐Sange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Over 279 pathogenic variants of the RS1 gene have been linked to XLRS ( 49 ). Gene therapy for RS1 holds significant promise to enhance the lives of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Over 279 pathogenic variants of the RS1 gene have been linked to XLRS ( 49 ). Gene therapy for RS1 holds significant promise to enhance the lives of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another proband exhibited the p.R102W mutation, resulting in macular schisis and retinal detachment. [ 28 ] Previous studies indicated a distinct spoke wheel pattern and foveal schisis in a 12-year-old boy with retinoschisis, attributed to the p.R102W mutation. [ 29 ] In addition, a study involving 86 Juvenile X-linked retinoschisis (JXLR) patients in the UK unveiled intrafamilial disparities in visual acuity associated with the same p.R102W mutations.…”
Section: Discussionmentioning
confidence: 99%